The Relationship between Research and Casework in Forensic Entomology - Martin J. R. Hall (Insects, 2021)
Research is a vital component of all forensic sciences and is often stimulated by casework, which identifies gaps in our knowledge. In such a niche area of forensic science as entomology there should be a close and mutually beneficial relationship between research and casework: to some extent there is a continuum between the two and many forensic entomologists are involved in both to a greater or lesser degree. However, research and casework involve quite differing challenges, from the replicated, highly controlled, sometimes esoteric aspects of research to the very individual, sometimes chaotic and disruptive, but highly applied aspects of casework. Ideally casework will include the full involvement of a forensic entomologist, who will collect the insect and climate evidence at the scene and produce a robust expert witness statement based on a full analysis of this data. Unfortunately, it can also include situations where samples, if collected at all, are poorly preserved, not representative of the full cadaver fauna available and presented to the entomologist months or years after the event, without local temperature data. While research is recognised through publications and their citation indices, casework and its associated expert witness statements often receive no credit in an academic workplace, although they do have a positive societal impact and many other benefits of teaching and public engagement value. This manuscript examines the relationship between research and casework from a UK perspective, to raise awareness of the need to create an environment that values the contribution of both, for future generations to flourish in both areas.